Heuristic methods for optimal coalition structure generation - Amir Hussin, Amir 'Aatieff; Fatima, Shaheen S. (Springer Verlag, 2017)
The problem of finding the optimal coalition structure arises frequently in multiagent systems. Heuristic approaches for solving this problem are needed because of its computational complexity. This paper studies two such approaches: tabu search and simulated annealing. Through simulations we show that tabu search generates better quality solutions than simulated annealing for coalition games in characteristic function form and those in partition function form.